1989
DOI: 10.1177/002580248902900303
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of the Use of Unusual Phenethylamine Compounds Sold as Illicit Amphetamine

Abstract: A 40-year-old man, who had regularly taken illicit amphetamine by intra-nasal inhalation for several years without ill effects, was admitted to hospital with signs of massive adrenergic overstimulation shortly after inhaling material which he had purchased in the belief that it was amphetamine. The administration of the beta-blocker practolol produced a paradoxical increase in blood pressure. After his discharge from hospital he suffered disabling feelings of anxiety for several weeks. Analysis of a sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…The described side effects in this report were mydriasis, hyperthermia, hypertension, tachycardia, insomnia, and anxiety. 39 These effects are in accordance with the described effects in other case and trip reports.…”
Section: Methylphenyl-amphetaminessupporting
confidence: 91%
See 1 more Smart Citation
“…The described side effects in this report were mydriasis, hyperthermia, hypertension, tachycardia, insomnia, and anxiety. 39 These effects are in accordance with the described effects in other case and trip reports.…”
Section: Methylphenyl-amphetaminessupporting
confidence: 91%
“…The suggested reasons for such deaths was on the one hand the increased serotonergic effects of 4-MA compared with amphetamine and on the other hand redosing due to underestimated onset or the dampened psychoactive effect when using 4-MA together with amphetamine. A trip report published by Bal et al in 1989 showed that 4-MA together with its N-methyl derivative has already been sold as amphetamine in the past. The described side effects in this report were mydriasis, hyperthermia, hypertension, tachycardia, insomnia, and anxiety.…”
Section: Methylphenyl-amphetaminesmentioning
confidence: 99%
“…Some may view this as an unnecessary approach for casework; however, a counterexample is the recent BALCO scandal where spectral interpretation of MS‐derived data was pivotal in determining the parent structure of the synthetic steroid tetrahydrogestrinone (THG) (16–19). Another example of the importance of mass spectral analysis is a case in which ring‐substituted amphetamine (para methyl—a regioisomer of compound VIII synthesized in this study) and p ‐methyl ring‐substituted methamphetamine sold as amphetamine caused an adverse reaction in a seasoned amphetamine user (20). The approach of the laboratory to determine the culprit molecule was identification by GC/MS, followed by “analysis of authentic samples of p ‐methyl(meth)amphetamine prepared in the laboratory.” Thus, it is not an unprecedented use of the tools of the forensic laboratory to use deconstructive fragmentation analysis of related compounds, followed by predictions of fragmentation and then synthesis of a compound to confirm the predictions.…”
mentioning
confidence: 99%
“…In this regard, it was described a massive adrenergic overstimulation just after inhaling material, which had been purchased in the belief that it was amphetamine but also contained 4-MA and dimethyl-amphetamine [3]. Only in one case, a patient with forensic evidence of 4-MA, developed extreme hyperthermia and died after cardiac arrest, although he had consumed ketamine, cocaine and other amphetamines 24 h before (EMCDDA-Europol report 2012).…”
Section: Introductionmentioning
confidence: 99%